Symmetric matrix: \(A^T=A\) ex: \( A= \begin{bmatrix} 5 & 2 & 1 \\ 2 & 7 & 5 \\ 1 & 5 & 8 \end{bmatrix} \) |
\(A\) is any square matrix. \(A+A^T\) is a symmetric. |
Proof:Suppose \(B=A+A^T\)\( (A+A^T)^T= A^T+(A^T)^T= A^T+A= A+A^T \) \(B^T=B\) |
Skew-symmetric matrix: \(A^T=-A\) ex: \( A= \begin{bmatrix} 0 & 3 & 2 \\ -3 & 0 & 4 \\ -2 & -4 & 0 \end{bmatrix} \) |
\(A\) is any square matrix. \(A-A^T\) is a skew-symmetric matrix. ** \(tr(A-A^T)=0\) |
Proof:Suppose \(B=A-A^T\)\( (A-A^T)^T= A^T-(A^T)^T= A^T-A= -(A-A^T) \) \(B^T=-B\) |